2012
DOI: 10.1039/c2an15949j
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependent sensing mechanism in sorted semi-conducting single walled nanotube based sensors

Abstract: Single walled carbon nanotube (SWCNT) networks present outstanding potential for the development of SWCNT-based gas sensors. Due to the complexity of the transport properties of this material, the physical mechanisms at stake during exposure to gas are still under debate. Previously suggested mechanisms are charge transfer between gas molecules and SWCNT and Schottky barrier modulation. By comparing electrical measurements with an analytical model based on Schottky barrier modulation, we demonstrate that one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…In low-density networks of non-sorted SWCNTs below the m-SWCNT perocolation threshold, conductance is increasingly dominated by Schottky barrier modulation at the interface between sc-SWCNT and the electrodes or m-SWCNTs, while thick networks have complete metallic conduction paths with the resistance of the film dominated by nanotube-nanotube junctions. 55 Accordingly, the effect of residual surfactant and water vapour was found to differ in thin (and thus lower density) networks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-density networks of non-sorted SWCNTs below the m-SWCNT perocolation threshold, conductance is increasingly dominated by Schottky barrier modulation at the interface between sc-SWCNT and the electrodes or m-SWCNTs, while thick networks have complete metallic conduction paths with the resistance of the film dominated by nanotube-nanotube junctions. 55 Accordingly, the effect of residual surfactant and water vapour was found to differ in thin (and thus lower density) networks.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness and density of randomly orientated SWCNT films is important when considering gas sensing mechanisms 52,53 and charge transport in the network. 54 Previous work by Battie et al 55 has shown that SWCNT sensing behaviour changes with a reduction in the number of m-SWCNTs in the film. Randeniya et al 56 found that thinner networks of SWCNTs are more influenced by the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…SWCNTs are considered as promising candidates for future optical and electronic devices such as field effect transistor, 1 gas sensors, 2,3 optical bolometer, 4 laser source, 5 and saturable absorber. 6 However, as shown previously, 3 the performances of these devices can be drastically affected by the chirality distribution.…”
mentioning
confidence: 94%
“…SWCNTs are sorted using non-linear DGU process as described by Gosh et al 13 Sorted SWCNT and raw SWCNTs are spread on cleaned glass substrates by filtration process. 2,3 Both films are composed of randomly orientated SWCNTs network and have a good optical quality. Their thickness, estimated from mechanical profilometry, is around 300 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation